Persepsi Kemudahan Penggunaan, Persepsi Kredibilitas, dan Persepsi Harga Terhadap Niat Nasabah Menggunakan Layanan Mobile Banking (Studi Kasus Pada Bank Syariah Mandiri Surabaya) - Reza Ramadhan; Sri Herianingrum (Jurnal Ekonomi Syariah Teori dan Terapan, 2017)
This study aims to discover the impact of Perceived Ease of Use, Perceived Credibility, and Perceived Price in Accordance Intention to Use Mobile Banking. This study uses the Theory Acceptance Model with quantitative approach using the Regression Linear Multivariate. The data source of this study uses primary data from questionnaire. The population characteristic in this study is the Client of Sharia Mandiri Bank that are not using Mobile Banking feature. The sample collecting technique used is Nonprobability Sampling with purposive sampling and accidental sampling. The result of the study shows that Perceived Ease of Use, Perceived Credibility, and Perceived Price in accordance significantly impacting towards the Interest in using the mobile banking feature of Bank Syariah Mandiri Surabaya. Suggestion towards Bank Syariah Mandiri to upgrade the security system to prevent the occurrence of crime trough the mobile banking feature so that the clients will feel safe in using transactions.